2021
DOI: 10.18203/2320-1770.ijrcog20211152
|View full text |Cite
|
Sign up to set email alerts
|

Changing trends of maternal mortality with its causes- ten years retrospective study in a peripheral medical college of West Bengal, India

Abstract: Background: The estimates of maternal mortality can only be used as a rough indicator of maternal health situation in any given country. High maternal mortality reflects not only in inadequacy of health care services for mothers, but also a low standard of living and socio economic status of the community. Objective was to assess the maternal mortality ratio (MMR), its probable causes and changing trends.Methods: The present study conducted at Midnapore Medical College (MMC), West Bengal. Data for analysis wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
1
0
0
Order By: Relevance
“…Additionally, the predominant number of deaths all occurred in health facilities compared to residential locations. These ndings are consistent with a study in the neighboring country of India, which showed that approximately 50-70% of maternal deaths occurred in the postpartum period, with 45% occurring in the rst 24 hours after delivery and two-thirds occurring during the rst week (15). A 25-year comprehensive analysis conducted in Ethiopia revealed that 45% of maternal deaths occurred within 42 days of childbirth, with 81% of those infants also dying (16).…”
Section: Discussionsupporting
confidence: 87%
“…Additionally, the predominant number of deaths all occurred in health facilities compared to residential locations. These ndings are consistent with a study in the neighboring country of India, which showed that approximately 50-70% of maternal deaths occurred in the postpartum period, with 45% occurring in the rst 24 hours after delivery and two-thirds occurring during the rst week (15). A 25-year comprehensive analysis conducted in Ethiopia revealed that 45% of maternal deaths occurred within 42 days of childbirth, with 81% of those infants also dying (16).…”
Section: Discussionsupporting
confidence: 87%